Detection, characterization and antimicrobial activity of nano silver against coconut yellow decline phytoplasmas in coconut and ornamental palms in Malaysia - Naderali, Neda (2015)
Phytoplasmas are prokaryotes within the class Mollicutes and have been associated with over 700 diseases in different plant species including agricultural crops and ornamentals universally. Detection and characterization of phytoplasmas are very difficult because of the inability to culture them in vitro. They inhabit the phloem tissue of plants at a very low concentration especially in woody monocotyledonous plant hosts. Symptoms such as yellowing of fronds particularly older leaves which eventually turned brown, the crown inflorescence yellowing, stunting and decline in growth. Popular evergreen ornamental palms which are infected by phytoplasma not only lose their green and vivid appearance but they harbour this pathogen as a source for next infection. Yellowing symptoms similar to coconut yellow decline phytoplasma disease have been observed on ornamental palms in Selangor, Malaysia. Extracted DNA was amplified from 15 symptomatic lipstick palms (Cyrtostachys renda), 15 foxtail palms (Wodyetia bifurcate), 15 royal palms (Roystonea regia) and 13 Red Coconut (MRD) palms (Cocos nucifera) by PCR using phytoplasma universal primer pair P1/P7 followed by R16F2n/ R16R2. Phytoplasma presence was confirmed and a 1250 bp product of 34 positive samples (12 of 15 symptomatic foxtail palms, 10 of 15 symptomatic lipstick palms and 12 of 15 symptomatic royal palms) was cloned and sequenced. R16F2n/ R16R2 is a specific primer for phytoplasma detection and a PCR product of approximately 1250 bp should be amplified using this primer. Sequence analysis indicated that the phytoplasmas associated with yellow disease on ornamental palms were belonging to 16SrI 'Candidatus Phytoplasma asteris' and 16SrXIV 'Candidatus Phytoplasma cynodontis' groups with accession numbers: KC924727 & KC924728 for lipstick phytoplasma, KF803561for royal phytoplasma, KC751560 & KC751561 for foxtail phytoplasma). Virtual RFLP analysis of the resulting profiles revealed that these palm-infecting phytoplasmas belonged to a subgroup most similar to 16SrI-B subgroup and a possibly new 16SrI-subgroup. In addition, because of low concentration of phytoplasma in coconut palm a real-time PCR assay with 16SCYD primer (specific primer for 16SrXIV group) was applied for sensitive detection of yellow decline phytoplasma in Malayan red coconut palms (MRD). Periwinkle phytoplasma was used as the reference gene for real-time PCR. The results revealed that this method is useful for sensitive detection of low titer phytoplasma in woody plants such as MRD coconut palms in comparison with nested-PCR. An antimicrobial activity of nano silver was tested against phytoplasma in yellow coconut palms andresulted in a significant reduction of phytoplasma concentration within five months of nano silver injection. Nano silver antimicrobial activity analysis with real-time PCR yielded a significant fluorescence signal (P<0.05). The results of SQ values were consistent with Ct values and concentration of CYD phytoplasma was decreased after applying nano silver (from 11.00 to 30.00 ng/μl). The values showed that, after applying nano silver, the concentration of the pathogen was decreased. This reduction was significant.